A theoretical framework for monetary analysis - Friedman, Milton (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1971)
This book examines the theoretical framework underlining the quantity theory of money as well as the Keynesian challenge to the quantity theory. It also assesses the dynamic implications of the monetary theory of National Income.
"Based on two papers: 'A theoretical framework for monetary analysis,' and 'A monetary theory of nominal income,' [by M. Friedman] which appeared in the Journal of political economy, volume 78, number 2, and volume 79, number 2, respectively."
Bibliography: p. 62-65.
usc 28/8/2017
Loans
Keywords: Quantity theory of money